2017
DOI: 10.1021/jacs.7b05436
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Palladium-Catalyzed Cycloisomerization: A Combined Experimental and Theoretical Study

Abstract: The cycloisomerization of enynes catalyzed by Pd(OAc) and bis-benzylidene ethylenediamine (bbeda) is a landmark methodology in transition-metal-catalyzed cycloisomerization. However, the mechanistic pathway by which this reaction proceeds has remained unclear for several decades. Here we describe mechanistic investigations into this reaction using enynamides, which deliver azacycles with high regio- and stereocontrol. Extensive H NMR spectroscopic studies and isotope effects support a palladium(II) hydride-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 101 publications
3
28
0
Order By: Relevance
“…These experiments suggest that AZB , along with the liquid additive, plays an important role in breaking of the trimeric structure to either a trimeric open structure, dimeric or even monomeric species (Scheme ). Similar ligand effect was observed for cycloisomerization of enynes catalyzed by [Pd(OAc) 2 ] 3 in solution . Taking into account that LAG reactions are faster than analogous ILAG reactions, we suggest that di‐ or monomeric species, which are formed in AcOH solution of [Pd(OAc) 2 ] 3 and NaOAc, are not prevailing in LAG but might occur under ILAG conditions.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These experiments suggest that AZB , along with the liquid additive, plays an important role in breaking of the trimeric structure to either a trimeric open structure, dimeric or even monomeric species (Scheme ). Similar ligand effect was observed for cycloisomerization of enynes catalyzed by [Pd(OAc) 2 ] 3 in solution . Taking into account that LAG reactions are faster than analogous ILAG reactions, we suggest that di‐ or monomeric species, which are formed in AcOH solution of [Pd(OAc) 2 ] 3 and NaOAc, are not prevailing in LAG but might occur under ILAG conditions.…”
Section: Resultssupporting
confidence: 74%
“…Similar ligand effect was observed for cycloisomerization of enynes catalyzed by [Pd(OAc) 2 ] 3 in solution. [20] Ta king into account that LAG reactions are fastert han analogous ILAG reactions, we suggest that di-or monomeric species, which are formed in AcOH solution of [Pd(OAc) 2 ] 3 and NaOAc, [21] are not prevailing in LAG butm ight occuru nder ILAG conditions. This is supported by PXRD (FigureS53)a nd IR ( Figure S36) analysis of the mixture obtained by IAG milling of [Pd(OAc) 2 ] 3 with NaOAc for 2hours.…”
Section: Mechanismmentioning
confidence: 84%
“…However, the exact role of the ligand BBEDA and its interaction with palladium pre-catalyst were unclear until Paton and Anderson delineated a combined experimental and theoretical study of the cycloisomerization of enynamides 6 to pyrrolidines 7 (Scheme 7). [12] Under experimental conditions, lesser conversion and slower rate of reaction were observed in the absence of BBEDA and water (Scheme 7). [12] Extensive 1 H NMR spectroscopic studies, a study of isotope effects, and computational studies supported a Pd(II)-hydride mediated pathway.…”
Section: Palladium-catalyzed Alder-ene Type Reactions Of Enynes 21 mentioning
confidence: 97%
“…[12] Under experimental conditions, lesser conversion and slower rate of reaction were observed in the absence of BBEDA and water (Scheme 7). [12] Extensive 1 H NMR spectroscopic studies, a study of isotope effects, and computational studies supported a Pd(II)-hydride mediated pathway. These studies also revealed the crucial roles of BBEDA, water, and the pre-catalyst [Pd(OAc) 2 ].…”
Section: Palladium-catalyzed Alder-ene Type Reactions Of Enynes 21 mentioning
confidence: 97%
See 1 more Smart Citation